Development of a Soybean Crushing Machine Based on the VDI 2221 Method at UKM Tempe Tiga Putra - Hilmi Syifa, Ahmad Zada; Ayudyah Eka Apsari (Universitas Medan Area, 2025)
UKM Tempe Tiga Putra, located in Jepara, faces challenges in the manual soybean crushing process. This process takes approximately 2 hours and 30 minutes per day to handle a daily capacity of 65 kg and imposes significant physical strain on workers, especially on the wrists. This study aims to design a more efficient and ergonomic soybean crusher using the VDI 2221 method. The resulting machine features specifications such as a ¼ hp AC motor, a hollow galvanized frame, an A-type V-belt, and dimensions tailored to the operator's anthropometry. The machine reduces processing time to 24 minutes per day, improving efficiency by 83.97%. The VDI 2221 method facilitated a design that meets the technical and economic requirements of the UKM while enhancing operator comfort. This innovation not only boosts production efficiency but also minimizes the risk of injury from manual labor. Consequently, the tool significantly enhances productivity and fosters a better working environment at UKM Tempe Tiga Putra.